Pc 1 pulsations observed at Cambridge Bay in the cusp region and Fort Smith in the auroral region - Kato, Yoshio; Tonegawa, Yutaka (National Institute of Polar Research, 1986)
P(論文) In order to understand the generation mechanism of daytime Pc 1 magnetic pulsations with 0.3-0.7Hz in the polar cusp and auroral regions, the authors analyzed the dynamic power spectra of the magnetic pulsations observed by the high sensitive induction magnetometer at Cmabridge Bay (Φ=76.8°⩘=299.6°) and Fort Smith (67.3°, 300.0°) during the period from 14 to 30 August 1974. It is found that Pc 1 pulsations having a patch-like structure were detected at Cambridge Bay in the cusp region near local noon, but were not observed at Fort Smith in the auroral region. On the other hand, during the period from 1300 to 1500 local time (LT) Pc 1 pulsations showing rising frequency with time appeared at Fort Smith in the sub-cleft region, while Pc 1 pulsations having rather stationary frequency were observed simultaneously at Cambridge Bay in the polar cusp region. After 1500LT, the patch-like Pc 1 pulsations disappeared at Cambridge Bay. From the spectrum analysis, a possible model for mechanism of excitation and propagation of daytime Pc 1 is proposed as follows; Pc 1 pulsations observed in the cusp region are the ion cyclotron wave which is excited near the dayside cusp magnetosheath boundary and propagates along the open field lines in the dayside cusp region. On the other hand, Pc 1 pulsations at Fort Smith in the auroral or sub-cleft region are the ion cyclotron wave, generated in the entry layer where the magnetic field is more intense than that in the magnetosheath. departmental bulletin paper